External shocks and macroeconomic responses in Nigeria: A global VAR approach - Lukman Oyeyinka Oyelami; P. A. Olomola (Cogent Economics & Finance, 2016)
This study investigates the macroeconomic responses of Nigerian economy to external shock between 1986 and 2014. Specifically, we examine the effect of oil price shocks and macroeconomic shocks from developed trading partners on Nigerian macroeconomic performances in order to establish pattern of reactions to these shocks in the country. We employ global vector autoregression (GVAR) comprising of the US, EU, China, Japan and Nigeria as the reference country. The adoption as of this method of estimation is necessitated by its capability to effectively model complex high-dimensional system and also offers adequate tools to deal with the curse of dimensionality that can arise from a study of this nature. Having critically examined the econometric properties of our GVAR model, the results from our estimation based on impulse response function show that oil price shocks have direct effect on real gross domestic product and exchange rate in Nigeria but variables like inflation and short-term interest rate do not show immediate response to the shocks. The results also indicate that macroeconomic variables such as short-term interest and inflation show immediate responses to shocks to counterpart variables in developed countries. Based on this, the study concludes that Nigerian economy is vulnerable to external shocks and such shocks are not limited to oil price shocks. Other form of shocks such as growth spillover and financial shocks from developed countries are also relevant in shaping the macroeconomic performances in Nigeria.
Keywords: 330; macroeconomics; GVAR; shock and price